2017
DOI: 10.18632/oncotarget.22188
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone may induce immunologic tolerance by activating the functions of decidual immune cells in early pregnancy

Abstract: The objective of this study was to investigate alterations in human first-trimester decidual immune cells (DICs) and relevant cytokines after treatment with prednisone. Decidual lymphocytes were treated with prednisone alone, cytokines alone or the combination of prednisone and cytokines. Levels of STAT3, STAT5, RORC and FOXP3 mRNA were assayed using quantitative real-time PCR, proportions of CD4+ T helper 17 (Th17) and CD4+ T regulatory (Treg) cells were measured using flow cytometry, and concentrations of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…12 Previous studies have observed a counterbalanced lymphocyte distribution in uRPL patients treated with PRS; thus, the treatment re-established the immune system presumed to be beneficial for embryo implantation. [21][22][23][24] The same effects have been observed in uRPL patients treated with IVIg. 22 25-27 For that reason, treatment before pregnancy with PRS and IVIg (PRS&IVIg) is expected to contribute to a favourable immunological environment in peripheral blood and the uterus which is expected to increase the chance of an uncomplicated pregnancy.…”
Section: Strengths and Limitations Of This Studysupporting
confidence: 67%
See 1 more Smart Citation
“…12 Previous studies have observed a counterbalanced lymphocyte distribution in uRPL patients treated with PRS; thus, the treatment re-established the immune system presumed to be beneficial for embryo implantation. [21][22][23][24] The same effects have been observed in uRPL patients treated with IVIg. 22 25-27 For that reason, treatment before pregnancy with PRS and IVIg (PRS&IVIg) is expected to contribute to a favourable immunological environment in peripheral blood and the uterus which is expected to increase the chance of an uncomplicated pregnancy.…”
Section: Strengths and Limitations Of This Studysupporting
confidence: 67%
“…Previous studies have observed a counterbalanced lymphocyte distribution in uRPL patients treated with PRS; thus, the treatment re-established the immune system presumed to be beneficial for embryo implantation 21–24. The same effects have been observed in uRPL patients treated with IVIg 22 25–27.…”
Section: Introductionmentioning
confidence: 53%
“…It has been demonstrated to be safe and effective in treating pregnancycomplicated immune diseases. 19,20 Regarding nutrient supplements, multivitamin containing folic acid reduces birth defects, especially malformation of the fetal neural tube. 21 Due to the limited efficacy of these single therapies in reducing the risk of spontaneous abortion, combination therapies have been designed and validated to improve live birth rate among women with URSA.…”
Section: Discussionmentioning
confidence: 99%
“…Prednisone is a glucocorticoid with immunosuppressive characteristics that is considered to prevent maternal immune rejection of the zygote during embryo implantation. It has been demonstrated to be safe and effective in treating pregnancy‐complicated immune diseases . Regarding nutrient supplements, multivitamin containing folic acid reduces birth defects, especially malformation of the fetal neural tube …”
Section: Discussionmentioning
confidence: 99%
“…The corticosteroid prednisone is clinically used in a variety of immune-related diseases and can promote the function and expansion of Tregs (Fu et al 2019). Indeed, in vitro prednisone treatment increased the proportion of Tregs among isolated first trimester decidual lymphocytes and inhibited Th17 cells (Fu et al 2017). Moreover, a clinical trial provided evidence that prednisone increased peripheral Tregs and improved pregnancy success in repeated implantation failure patients (Huang et al 2021).…”
Section: R26mentioning
confidence: 99%